Particle control in long-pulse discharge using divertor pumping in LHD. (1st March 2022) - Motojima, G; Masuzaki, S; Morisaki, T; Watanabe, K Y; Kobayashi, M; Ida, K; Sakamoto, R; Yoshinuma, M; Seki, R; Nuga, H; Tsujimura, T; Suzuki, C; et al.
Abstract: Density control is crucial for maintaining stable confined plasma. Divertor pumping, where neutral particles are compressed and exhausted in the divertor region, was developed for this task for the Large Helical Device. In this study, neutral particle pressure, which is related to recycling, was systematically scanned in the magnetic configuration by changing the magnetic axis position. High neutral particle pressure and compression were obtained in the divertor for a high plasma electron density and the inner magnetic axis configuration. Density control using divertor pumping with gas puffing was applied to electron cyclotron heated plasma in the inner magnetic axis configuration, which provides high neutral particle compression and exhaust in the divertor. Stable plasma density and electron temperature were maintained with divertor pumping. A heat analysis shows that divertor pumping did not affect edge electron heat conductivity, but it led to low electron heat conductivity in the core caused by electron-internal-transport-barrier-like formation.